2019
DOI: 10.1038/s41396-019-0377-0
|View full text |Cite
|
Sign up to set email alerts
|

Taming chlorophylls by early eukaryotes underpinned algal interactions and the diversification of the eukaryotes on the oxygenated Earth

Abstract: Extant eukaryote ecology is primarily sustained by oxygenic photosynthesis, in which chlorophylls play essential roles. The exceptional photosensitivity of chlorophylls allows them to harvest solar energy for photosynthesis, but on the other hand, they also generate cytotoxic reactive oxygen species. A risk of such phototoxicity of the chlorophyll must become particularly prominent upon dynamic cellular interactions that potentially disrupt the mechanisms that are designed to quench photoexcited chlorophylls i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Previous studies have reported that dark orange or reddish-brown to dark brown globules are commonly observed within Euglenida cells in aged cultures [ 25 , 26 ]. Consistent with this, we observed several brown globules within cells from 1- or 2-month-old cultures ( Figure 1 B; Supplementary Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that dark orange or reddish-brown to dark brown globules are commonly observed within Euglenida cells in aged cultures [ 25 , 26 ]. Consistent with this, we observed several brown globules within cells from 1- or 2-month-old cultures ( Figure 1 B; Supplementary Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, we observed several brown globules within cells from 1- or 2-month-old cultures ( Figure 1 B; Supplementary Figure S2 ). Kashiyama et al [ 26 ] isolated the brown globules from E. gracilis cells, and determined that they contained chlorophyll- a -derived 13 2 ,17 3 -cyclopheophorbides a enol (cPPB- a E) and related compounds. Since cPPB- a E and its derivatives gradually accumulate in E. gracilis cells after the stationary phase, Kashiyama et al [ 26 ] concluded that globule formation was associated with 13 2 ,17 3 -cyclopheophorbide enol (CPE)-accumulating chlorophyll catabolism (CACC) during chloroplast dismantling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). In E. gracilis cultivated under dark conditions, chloroplasts are degraded, but brown granules remain in the cells [34]. These granules are reported to be massive membrane structures generated from degraded thylakoids [34].…”
Section: Ph-dependent Production Of Glutamate Glutamine and Succinamentioning
confidence: 99%
“…Naturally occurring chlorophylls (Chls) primarily function as photosynthetic pigments, and are observed in metabolites of phototrophs as well as in aqueous environments and sediments They have various molecular structures with three types of cyclic tetrapyrroles . Bacteriochlorophyll(BChl)‐ a is found in anoxygenic photosynthetic bacteria.…”
Section: Introductionmentioning
confidence: 99%